K-Workers Practice in Increasing Graduate Employability to Overcome the Challenges of the Fourth Industrial Revolution - Massetor, Noor Arif; Rozali, Mohd Zulfadli; Marian, Mohd Fairuz (Research and Innovation in Technical and Vocational Education and Training, 2021)
The low employability rate among Vocational College (VC) graduates compared to TVET institutions such as Polytechnics and Community Colleges is an issue in this study. Coupled with the wave of Fourth Industrial Revolution which will challenge VC graduates to find employment opportunities in the growing industrial sector now. This problem arises due to the lack of elements of K-worker competency elements in the curriculum of VC students and the lack of emphasis on the concept of IR 4.0 makes them insensitive to what is happening in the industry nowadays. K-worker is a term for "white collar" introduced by Peter Drucker in 1959 and is an important component for an employees to be accepted by the employers. The purpose of this study was to identify the perceptions of the college vocational students in diploma vocational (DVM) of welding technology about K-worker competency to overcome the challenges of the Fourth Industrial Revolution (IR 4.0). Quantitative research design by using the questionnaire were applied which has various sections related to demographics, technical competency, social and humanity competency, learning and methodology competency with Likert scale 5 for each item. Only 52 respondents who were selected as the study sample were students are from Batu Pahat Vocational College and Kluang Vocational College. Research findings shows that diploma students in technology welding has good individual knowledge in technical competency but lacks in individual skills. Further, respondents have good teamwork in social and humanity competency but lack in communication skills. Also, the overall findings show that students of diploma welding technology had lifelong learning and information management skills at a good level in their learning and methodology competency. The findings also shows a strong positive relationship between learning and methodology competency with humanity and social competency. In summary, this study also discusses the findings of the study with previous studies as well as further research proposals to help prospective VC graduates to face the challenges of IR 4.0.